INVESTIGATION OF THE ARMENIAN POWER SYSTEM OPERATING REGIME INFLUENCE ON VALUE OF TECHNICAL POWER LOSSES IN TRANSMISSION NETWORKS - T. S. Gnuni (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper analyzes an influence of operating parameters of the Armenian Power System (PS) on the value of technical power losses in the 110–220 kV transmission networks. Methods of regression and variance analyses are used in this paper. A number of calculation experiments have been carried out and such factors as power supply of the Armenian Power System, power flow between the Armenian and Iranian Power Systems, total load of the Armenian Power System, power export from the Armenian Power System to the Georgian Power System have been taken as the influencing ones. The obtained regression equations reflect the most common tendencies of the Armenian Power System behavior and allow to draw a conclusion regarding the nature of its operating parameters’ influence on the value of technical power losses in transmission networks that means to restrict the field of solution search, directed to the reduction of technical losses.